1998
DOI: 10.1046/j.1460-2695.1998.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Growth Behaviour of Sm45c Steel Under Mixed‐mode I and Ii Loading

Abstract: The practical applications of studies related to constant amplitude mode I loading are somewhat limited in situations where more than one mode exists. So, criteria, rules and laws for these situations have to be validated with experiments. This paper extends previous results by the authors for mixed‐mode I and II fatigue loading. An effective stress intensity factor range which considers crack closure and crack surface interference is described for the analysis of a crack under mixed‐mode I and II fatigue load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Estimation of fatigue crack growth was also performed in complex loading conditions [76]. You and Lee [115] evaluated the crack behaviour of steel in mixed-mode I and mode II loadings. Their studies revealed the accelerated crack growth by the addition of cyclic mode II.…”
Section: Challenge-3: Intricacy In Fatigue Crack Propagationmentioning
confidence: 99%
“…Estimation of fatigue crack growth was also performed in complex loading conditions [76]. You and Lee [115] evaluated the crack behaviour of steel in mixed-mode I and mode II loadings. Their studies revealed the accelerated crack growth by the addition of cyclic mode II.…”
Section: Challenge-3: Intricacy In Fatigue Crack Propagationmentioning
confidence: 99%
“…Therefore, development of a crack growth criterion and collection of test data for mixed mode fracture are important and necessary for potential structural applications. The angled crack problem has been given special attention in the recent years by fracture mechanics investigators 1–5 . However, most of the investigations were focused on the fracture of plates, each of which containued an inclined through crack, subjected to mixed‐mode I and II loading conditions.…”
Section: Introductionmentioning
confidence: 99%